Case Report: A rare case of antenatally diagnosed mature adrenal teratoma in an infant: insights and literature review - Msarweh, Amar; Shehadeh, Mohammad Hakam; Abualrub, Ahmad M.; Malhes, Waleed M.; Msarweh, Nadeen; Sinokrot, Jenan Khaled; Aliwisat, Ahmed H. (Frontiers in Pediatrics, 2024)
Teratomas are germ cell tumors that arise from the derivatives of the three germ cell layers. They are categorized into subtypes by the extent of maturation, with mature teratomas being the most common subtype. While they can arise in various extragonadal regions, including the retroperitoneum, their occurrence in the retroperitoneal space is extremely rare. It is even more exceptional for these tumors to be located within the adrenal gland. In this report, we describe an 18-day-old female infant who presented with a left suprarenal mass. The mass was detected during prenatal screening via ultrasound at 30 weeks of pregnancy. Evaluation after birth, including a chest and abdomen computed tomography (CT) scan, revealed a large, well-defined left suprarenal mass. The mass was surgically resected and found to measure 9 cm x 7 cm × 5 cm. Histopathological examination confirmed a cystic mature teratoma containing a variety of well-differentiated tissues. The patient has shown excellent progress over the 1-year follow-up, with no evidence of recurrence. Only a few cases of mature adrenal teratoma have been reported, highlighting the importance of this case report.